THE EFFECT OF STRUCTURED ACADEMIC CONTROVERSY MODEL ON STUDENTS' ARGUMENTATION ABILITY IN ECONOMIC SUBJECTS: AN EMPIRICAL STUDY - FH, Yuliana; Anggriani, Desi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Structured Academic Controversy (SAC) is a learning model that develops learners' critical and argumentative thinking skills through structured debates from two different points of view. In learning economics, argumentation skills are important because they train students to think logically, express opinions, and make rational decisions. This study aims to determine the effect of applying the SAC model on improving students' argumentation skills in class X economics subjects at SMA Negeri 10 Palembang. The method used is quantitative with a One Group Pretest-Posttest type Quasi Experimental design. Data were obtained through tests and observations. The results showed that the average pretest score of students was 58.96 and increased to 84.3 in the posttest. The t-test results show that the tcount is 12.144 > table 2.030 so Ho is rejected and Ha is accepted. This proves that the SAC model has a significant effect on improving argumentation skills. In addition, the observation of students' activities also showed an increase, namely 75% in the first meeting, 86.9% in the second meeting, and 97.6% in the third meeting, which reflected the effectiveness of the SAC learning model